Local Wisdom of Minority Religious Groups in Indonesia in Humanitarian and Philanthropic Activities Covid-19 Pandemic - Noor, Nina Mariani; Ro'fah; Hanjarwati, Astri; Aula, Siti Khadijah Nurul (IBDA` : Jurnal Kajian Islam dan Budaya, 2024)
COVID-19 has impacted people’s lives worldwide as a global pandemic. It is a shocking health issue and generates other economic and societal problems. With its many citizens, Indonesia faces limitations in dealing with this pandemic. The research was initiated due to global COVID-19, which affects Indonesia economically and socially. They utilized local wisdom to support religious minorities via humanitarian efforts. This research explores the charitable and philanthropic efforts of minority religious communities such as Ahmadiyah, Shia, Baha'i, and Sapta Dharma in Yogyakarta, which often face negative perceptions in Indonesia. This study uses qualitative methods to illustrate how minority religious groups participate in helping others in responding to the pandemic. Data was collected through in-depth interviews, Focused Group Discussions, and documentation. The results showed that minority religious groups in Indonesia have the initiative and actively participate in assisting needy people around them as their responsibility as Indonesian citizens, despite the discrimination and hostility they face because of their beliefs. Philanthropic motivations based on religious values, universal humanity, and moral responsibility as a religious group can be viewed as local wisdom. The existence of cultural views in Indonesia for help and mutual assistance makes aid acceptable as a form of brotherhood, which is inversely proportional to the theological rejection of the group.